Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Explore a wealth of knowledge from professionals across different disciplines on our comprehensive platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Sure, let's solve the problem step-by-step.
Given the function:
[tex]\[ y = \ln\left(e^{3x^2} - \cos^9(x^2 + 3)\right) \][/tex]
We need to find the derivative \(\frac{dy}{dx}\).
Step 1: Identify the outer function and the inner function.
[tex]\[ u = e^{3x^2} - \cos^9(x^2 + 3) \][/tex]
[tex]\[ y = \ln(u) \][/tex]
Step 2: Use the chain rule of differentiation.
[tex]\[ \frac{dy}{dx} = \frac{dy}{du} \cdot \frac{du}{dx} \][/tex]
Since \( y = \ln(u) \),
[tex]\[ \frac{dy}{du} = \frac{1}{u} \][/tex]
Step 3: Differentiate the inner function \( u \) with respect to \( x \).
[tex]\[ u = e^{3x^2} - \cos^9(x^2 + 3) \][/tex]
[tex]\[ \frac{du}{dx} = \frac{d}{dx}\left(e^{3x^2}\right) - \frac{d}{dx}\left(\cos^9(x^2 + 3)\right) \][/tex]
Step 4: Differentiate \( e^{3x^2} \) with respect to \( x \).
[tex]\[ \frac{d}{dx}\left(e^{3x^2}\right) = e^{3x^2} \cdot \frac{d}{dx}(3x^2) \][/tex]
[tex]\[ \frac{d}{dx}(3x^2) = 6x \][/tex]
So,
[tex]\[ \frac{d}{dx}\left(e^{3x^2}\right) = 6x \cdot e^{3x^2} \][/tex]
Step 5: Differentiate \( \cos^9(x^2 + 3) \) with respect to \( x \).
Using the chain rule again, let \( v = \cos(x^2 + 3) \), so \(\cos^9(x^2 + 3) = v^9\).
[tex]\[ \frac{d}{dx}\left(\cos^9(x^2 + 3)\right) = 9\cos^8(x^2 + 3) \cdot \frac{d}{dx}\left(\cos(x^2 + 3)\right) \][/tex]
Now, differentiate \( \cos(x^2 + 3) \):
[tex]\[ \frac{d}{dx}\left(\cos(x^2 + 3)\right) = -\sin(x^2 + 3) \cdot \frac{d}{dx}(x^2 + 3) \][/tex]
[tex]\[ \frac{d}{dx}(x^2 + 3) = 2x \][/tex]
So,
[tex]\[ \frac{d}{dx}\left(\cos(x^2 + 3)\right) = -2x \sin(x^2 + 3) \][/tex]
[tex]\[ \frac{d}{dx}\left(\cos^9(x^2 + 3)\right) = 9 \cdot \cos^8(x^2 + 3) \cdot (-2x \sin(x^2 + 3)) \][/tex]
[tex]\[ = -18x \cos^8(x^2 + 3) \sin(x^2 + 3) \][/tex]
Step 6: Combine the results from Steps 4 and 5.
[tex]\[ \frac{du}{dx} = 6x \cdot e^{3x^2} - 18x \cos^8(x^2 + 3) \sin(x^2 + 3) \][/tex]
Step 7: Substitute back into the chain rule expression.
[tex]\[ \frac{dy}{dx} = \frac{1}{u} \cdot \frac{du}{dx} \][/tex]
[tex]\[ = \frac{1}{e^{3x^2} - \cos^9(x^2 + 3)} \cdot (6x e^{3x^2} - 18x \cos^8(x^2 + 3) \sin(x^2 + 3)) \][/tex]
[tex]\[ = \frac{6x e^{3x^2} - 18x \cos^8(x^2 + 3) \sin(x^2 + 3)}{e^{3x^2} - \cos^9(x^2 + 3)} \][/tex]
Therefore, the derivative is:
[tex]\[ \frac{dy}{dx} = \frac{6x e^{3x^2} + 18x \sin(x^2 + 3) \cos^8(x^2 + 3)}{e^{3x^2} - \cos^9(x^2 + 3)} \][/tex]
Given the function:
[tex]\[ y = \ln\left(e^{3x^2} - \cos^9(x^2 + 3)\right) \][/tex]
We need to find the derivative \(\frac{dy}{dx}\).
Step 1: Identify the outer function and the inner function.
[tex]\[ u = e^{3x^2} - \cos^9(x^2 + 3) \][/tex]
[tex]\[ y = \ln(u) \][/tex]
Step 2: Use the chain rule of differentiation.
[tex]\[ \frac{dy}{dx} = \frac{dy}{du} \cdot \frac{du}{dx} \][/tex]
Since \( y = \ln(u) \),
[tex]\[ \frac{dy}{du} = \frac{1}{u} \][/tex]
Step 3: Differentiate the inner function \( u \) with respect to \( x \).
[tex]\[ u = e^{3x^2} - \cos^9(x^2 + 3) \][/tex]
[tex]\[ \frac{du}{dx} = \frac{d}{dx}\left(e^{3x^2}\right) - \frac{d}{dx}\left(\cos^9(x^2 + 3)\right) \][/tex]
Step 4: Differentiate \( e^{3x^2} \) with respect to \( x \).
[tex]\[ \frac{d}{dx}\left(e^{3x^2}\right) = e^{3x^2} \cdot \frac{d}{dx}(3x^2) \][/tex]
[tex]\[ \frac{d}{dx}(3x^2) = 6x \][/tex]
So,
[tex]\[ \frac{d}{dx}\left(e^{3x^2}\right) = 6x \cdot e^{3x^2} \][/tex]
Step 5: Differentiate \( \cos^9(x^2 + 3) \) with respect to \( x \).
Using the chain rule again, let \( v = \cos(x^2 + 3) \), so \(\cos^9(x^2 + 3) = v^9\).
[tex]\[ \frac{d}{dx}\left(\cos^9(x^2 + 3)\right) = 9\cos^8(x^2 + 3) \cdot \frac{d}{dx}\left(\cos(x^2 + 3)\right) \][/tex]
Now, differentiate \( \cos(x^2 + 3) \):
[tex]\[ \frac{d}{dx}\left(\cos(x^2 + 3)\right) = -\sin(x^2 + 3) \cdot \frac{d}{dx}(x^2 + 3) \][/tex]
[tex]\[ \frac{d}{dx}(x^2 + 3) = 2x \][/tex]
So,
[tex]\[ \frac{d}{dx}\left(\cos(x^2 + 3)\right) = -2x \sin(x^2 + 3) \][/tex]
[tex]\[ \frac{d}{dx}\left(\cos^9(x^2 + 3)\right) = 9 \cdot \cos^8(x^2 + 3) \cdot (-2x \sin(x^2 + 3)) \][/tex]
[tex]\[ = -18x \cos^8(x^2 + 3) \sin(x^2 + 3) \][/tex]
Step 6: Combine the results from Steps 4 and 5.
[tex]\[ \frac{du}{dx} = 6x \cdot e^{3x^2} - 18x \cos^8(x^2 + 3) \sin(x^2 + 3) \][/tex]
Step 7: Substitute back into the chain rule expression.
[tex]\[ \frac{dy}{dx} = \frac{1}{u} \cdot \frac{du}{dx} \][/tex]
[tex]\[ = \frac{1}{e^{3x^2} - \cos^9(x^2 + 3)} \cdot (6x e^{3x^2} - 18x \cos^8(x^2 + 3) \sin(x^2 + 3)) \][/tex]
[tex]\[ = \frac{6x e^{3x^2} - 18x \cos^8(x^2 + 3) \sin(x^2 + 3)}{e^{3x^2} - \cos^9(x^2 + 3)} \][/tex]
Therefore, the derivative is:
[tex]\[ \frac{dy}{dx} = \frac{6x e^{3x^2} + 18x \sin(x^2 + 3) \cos^8(x^2 + 3)}{e^{3x^2} - \cos^9(x^2 + 3)} \][/tex]
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.